Peningkatan Sarana Olahraga Desa Sinar Bhakti Melalui Aksi Gotong Royong - Ibrahim Husin Djasuli; M Thoriq Alfarras; Wahyu Wardani; Lydia Apriliani; Mailani Rabiulkhri (Institut Teknologi dan Bisnis Semarang, 2025)
Sports activities in Sinar Bhakti Village are hindered by the poor condition of the volleyball court, which is uneven and riddled with potholes. This condition not only makes sports activities uncomfortable but also increases the risk of injuries, especially for children and teenagers. Consequently, community interest in utilizing the court as a venue for sports and social activities has declined. This Community Service Program (PKM) aimed to improve the condition of the volleyball court by patching the potholes with cement through a collective action approach. The method involved active participation from the villagers, starting from resource mobilization to the implementation of the court repairs. In addition to improving the quality of sports infrastructure, this activity also served as a medium to strengthen the sense of community among the residents. The results showed that the repaired volleyball court is now safer and more comfortable for various activities, such as sports training and local tournaments. This improved facility is expected to encourage increased sports activities, strengthen social relationships among residents, and create a more productive gathering space in Sinar Bhakti Village.